TINGKAT EFISIENSI BANK DI INDONESIA - Rubeda Kalis; Pujiati Amin; P. Eko Prasetyo (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
This study aims to analyze the efficiency of banks in Indonesia period 2007-2009.The tools of analysis is  Data Envelopment Analysis (DEA). It uses data financial statemens and supplied by Bank Indonesia. The research shows that  in general the performance of banks in Indonesia is inefisiency. Bank that have efficiency is BRI, BTN, BPD Jabar, BPD Jatim, BPD Riau, Bank Niaga dan Bank Muamalat. This fact shows  the banks in Indonesia have not been up to the wasteful use of cost on several input variables  in their economic activities. Key words: Efficiency, bank, Indonesia, DEA